2017
DOI: 10.1063/1.4993972
|View full text |Cite
|
Sign up to set email alerts
|

Spectral up- and downshifting of Akhmediev breathers under wind forcing

Abstract: We experimentally and numerically investigate the effect of wind forcing on the spectral dynamics of Akhmediev breathers, a wave-type known to model the modulation instability. We develop the wind model to the same order in steepness as the higher order modifcation of the nonlinear Schroedinger equation, also referred to as the Dysthe equation. This results in an asymmetric wind term in the higher order, in addition to the leading order wind forcing term. The derived model is in good agreement with laboratory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Figure 1(c) shows the mean up-shifts during forcing and downshifts during damping as discussed in [10]. A similar trend, but in the sense of widening and narrowing is seen for the bandwidth (Figure 1d).…”
Section: A Temporal Evolutionsupporting
confidence: 62%
See 3 more Smart Citations
“…Figure 1(c) shows the mean up-shifts during forcing and downshifts during damping as discussed in [10]. A similar trend, but in the sense of widening and narrowing is seen for the bandwidth (Figure 1d).…”
Section: A Temporal Evolutionsupporting
confidence: 62%
“…Our model to propagate the envelope a(x, t) is the space-like version of the forced/damped-Modified NLS (MNLS) equation [10], with higher order terms added to suppress unphysical resonances and improve numerical stability. See Appendix A for a full derivation and notations.…”
Section: A Model Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other experiments, the effect of wind on rogue wave dynamics has been studied in specially adapted wind-sea wave tanks [159]. Particular experiments in a one-dimensional wave tank have shown that wind can induce frequency downshifting in the spectrum of initial breather solutions excited by a wavemaker [160,161], while other experiments in an annular wave tank did not use any initial mechanical wave generation, but allowed waves to develop spontaneously from the action of the wind on the water's surface [145]. These results are shown in Fig.…”
Section: Wave Tank Experimentsmentioning
confidence: 99%